Speech audiometry for indication of conventional and implantable hearing aids - Hoppe, Ulrich; Hast, A. (HNO, 2017)
The social function of the human hearing apparatus is comprehension of speech. Auditory rehabilitation aims to enhance speech perception in everyday life. Consequently, audiological evaluation contains speech perception measurement. Many speech audiometric methods have been developed in German-speaking countries, which are suitable for quantification of speech perception abilities in quiet and in noise to address specific diagnostic questions. For establishment of the indication for technical hearing systems such as hearing aids and cochlear implants, the Freiburg monosyllabic test has been employed successfully for many years. Particularly sentence tests have been suggested as a complementary measure for hearing aid indication and assessment. This paper describes the characteristics and range of application of various speech audiometric methods, and highlights the methodological limitations of the individual tests.
EVALuna2:33173